Self-assembly in tailor-made polyfluorenes: synergistic effect of porous spherical morphology and fret for visual sensing of bilirubin - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2013)
Two new fluorene-based homo- (PDP-PF) and copolymers (PDPPF-co-Ph) were synthesized with a bulky 3-pentadecylphenoxy (PDP) group appended hexyl chains at the 9, 9' position using Suzuki coupling polymerization. Investigation on the morphology of the polymers using microscopic techniques like TEM and AFM indicated formation of self-assembled nanostructures like vesicles by PDP-PF and porous spheres by PDPPF-co-Ph respectively. Dynamic as well as static light scattering studies (DLS, SLS) in THF also indicated the existence of self-assembled nanosized particles in solution with a shape factor (rho) of 0.76 and 0.96 for PDP-PF and PDPPF-co-Ph, respectively, confirming the existence of vesicles in the case of the former and spherical particles in the case of the latter polymer. The favorable photophysical properties of the polyfluorenes were taken advantage of for the selective sensing of unbound bilirubin (BR) in THF. A high energy transfer efficiency of 86% upon addition of bilirubin with color change from blue (polyfluorene emission) to green (FRET-induced bilirubin emission) was observed with PDPPF-co-Ph. Steady state fluorescence measurements gave a minimum donor-acceptor distance of 36 A(0) and time-resolved fluorescence decay measurements showed a reduction in average lifetime of PDPPF-co-Ph (from 450 to 240 ps) upon addition of bilirubin indicating efficient energy transfer. The open porous spherical assembly of PDPPF-co-Ph enabled better adsorption of the analyte, which along with the good spectral overlap resulted in greater efficiency for FRET-induced energy transfer. Sensing of unbound bilirubin was also attempted in THF/water solvent mixture in an effort to simulate the unbound (THF soluble) and bound (water-soluble) bilirubin equilibrium. Enhancement of bilirubin emission coupled with quenching of polyfluorene emission makes this approach adaptable for visual fluorimetric color change (blue to green) based sensor. Structural analogues such as biliverdin and porphyrin showed poor fluorescence quenching efficiency, thus highlighting the selectivity and sensitivity of the FRET-based sensing of bilirubin by the newly designed polyfluorene.

Selective and sensitive sensing of free bilirubin in human serum using water-soluble polyfluorene as fluorescent probe - Senthilkumar, T.; Asha, S. K. (Macromolecules, 2015)
The adherence of serum protein on conjugated polymer is a major bottleneck in the application of the latter for selective sensing of small biomolecules in blood serum. In this report, we present new polyfluorenes with d-glucuronic acid appendage that is a nonreceptor for any serum protein, thereby providing a platform for selective sensing of free bilirubin in the clinically relevant range of <25 to >50 mu mol/L in human blood serum. The appended d-glucuronic acid formed noncovalent interactions with bilirubin, which in conjunction with favorable spectral overlap between the polymers and bilirubin facilitated efficient FRET process in aqueous solutions. Addition of bilirubin resulted in the quenching of the polyfluorene emission with simultaneous appearance of bilirubin emission exhibiting visual emission color change from blue to light green. The polymer remained stable in serum even under severe basic conditions and exhibited high selectivity with visual sensitivity only toward free bilirubin in human serum in the presence of crucial interferences such as hemoglobin, proteins, biliverdin, glucose, cholesterol, and metal ions. Nanomolar sensing of bilirubin could also be demonstrated successfully using one of the d-glucuronic acid appended polymer (PF-Ph-GlcA), which could sense similar to 150 nm of bilirubin in human serum. The combined role of energy transfer and noncovalent interaction highlights the potential of the new polymer design for highly selective sensing activity in complex biofluids.